2022
DOI: 10.3390/atmos13010130
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Southwest Monsoon Surge and the Heavy Rainfall Associated with Landfalling Super Typhoon Rammasun

Abstract: Based on the China Meteorological Administration (CMA) best-track data, the ERA5 reanalysis, and the Global Precipitation Measurement (GPM) precipitation data, this paper analyzes the reasons for the heavy rainfall event of Super Typhoon Rammasun in 2014, and the results are as follows: (1) Rammasun was blocked by the western Pacific subtropical high (WPSH), the continental high, and the mid-latitude westerly trough. Such a stable circulation pattern maintained the vortex circulation of Rammasun. (2) During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previously, the monsoon surge was often defined as the regional average of the 850-hPa zonal wind over the designated area (Dong et al, 2010). However, considering the east-west movement of typhoons in the Northwest Pacific, the dynamic monsoon surge index (DMSI) (Zhao et al, 2021;Liu et al, 2022b) is used to distinguish between the typhoon circulation and monsoon surge circulation before and after typhoon landfall, which is defined as:…”
Section: Dynamic Monsoon Surge Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the monsoon surge was often defined as the regional average of the 850-hPa zonal wind over the designated area (Dong et al, 2010). However, considering the east-west movement of typhoons in the Northwest Pacific, the dynamic monsoon surge index (DMSI) (Zhao et al, 2021;Liu et al, 2022b) is used to distinguish between the typhoon circulation and monsoon surge circulation before and after typhoon landfall, which is defined as:…”
Section: Dynamic Monsoon Surge Indexmentioning
confidence: 99%
“…The results show that they are positively correlated and associated with precipitation enhancement. Additional studies have shown that due to the low-frequency oscillation of the East Asian summer monsoon, the monsoon surge features a northward propagation, which continues to provide water vapor for typhoons, thus affecting the heavy rainfall in typhoons (Liu et al, 2022a). Therefore, how monsoon flow affects typhoon activity, especially regarding its impact on heavy precipitation, needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the frequency of landfalling typhoons in southern China has increased since the year 2000 [8][9][10]. Tropical cyclones such as Haiyan (in 2013), Rammasun (in 2014), and Mangkhut (in 2018) have caused tremendous damages in southern China [11][12][13]. In addition to the intensity and track of tropical cyclones, the spatial distribution of the population is also an important factor in exposing people to the hazardous tropical cyclones events.…”
Section: Introductionmentioning
confidence: 99%